Conjugated Platinum-Poly-Ynes with extended Arylene Ethynylenes (Journal of Bangladesh Academy of Sciences, 2015)
The platinum-poly-yne polymers poly[trans-bis(tri-n-butylphosphine) platinum-poly (4,4´- diethynylenearylene)] (arylene = biphenylene 3 and anthracene 4) were synthesized by the condensation reaction between poly(diethynylenearylene) (arylene = biphenylene 1 and anthracene 2) and trans-[(PnBu3)2PtCl2] in diisopropyl amine and dichloromethane under nitrogen atmosphere in the presence of CuI catalyst. The newly synthesized platinum containing poly-yne polymers exhibit good solubility in common organic solvents. These metal linked polymers were characterized by IR, 1H NMR and 31P NMR spectroscopy.Journal of Bangladesh Academy of Sciences, Vol. 39, No. 2, 195-202, 2015